Girl on Fire – Links between sex, firefighters’ clothing, safety, confidence and wear and tear - Rahel Krause; Justin Kühn; Carsten Schiffer; Thomas Gries (Communications in Development and Assembling of Textile Products)
Firefighters are exposed to high risks and hazards, such as flames and smoke, in their daily lives. To be protected against these risks, firefighters wear protective clothing. As an employer, it is the duty to provide firefighters with good protection according to DIN EN 469. To do so, it is necessary to select, procure and maintain suitable firefighters' protective clothing. In order to identify weaknesses in the above steps and to develop and present proposals for remedying the identified weak points, an empirical study was conducted. In preparation for this study, interviews were first conducted with members of fire brigades. Based on the interviews, the relevant standards and regulations for fire fighters´ clothing were classified and areas of tension between the standards and regulations as well as their design in everyday fire brigade life were identified. Based on this, a standardized quantitative survey was conducted and the answers of the respondents were empirically evaluated. The evaluation examined both the respondents' answering behavior and the dependency between the answering behavior for different questions due to demographic differences. A key finding is that women firefighters are less satisfied with their firefighting clothing compared to men firefighters. The firefighters' clothing fits them worse. They do not feel as safe and comfortable. Moreover, woman have less confidence in the protective clothing. There is a correlation between the fit of the clothing and the satisfaction, confidence and feeling of protection